3D magnetic nanocomposite scaffolds enhanced the osteogenic capacities of rat bone mesenchymal stem cells in vitro and in a rat calvarial bone defect model by promoting cell adhesion. Issue 9 (20th April 2021) - Han, Liping; Guo, Yu; Jia, Lu; Zhang, Qian; Sun, Liuxu; Yang, Zukun; Dai, Yang; Lou, Zhichao; Xia, Yang
Abstract: Magnetic scaffolds incorporated with iron oxide nanoparticles (IONPs) are biocompatible and present excellent osteogenic properties. However, the underlying mechanism is unclear. In this study, 3D‐printed poly(lactic‐co‐glycolic acid) scaffolds were coated with IONPs using layer‐by‐layer assembly (Fe‐scaffold) to prepare magnetic scaffolds. The effects of this modification on osteogenesis were investigated by comparison with untreated scaffolds (Uncoated‐scaffold). The results showed that the proliferation of rat bone mesenchymal stem cells (rBMSCs) on the Fe‐scaffold was enhanced compared with those on the Uncoated‐scaffold ( p < 0.05). The alkaline phosphatase activity and expression levels of osteogenic‐related genes of cells on the Fe‐scaffold were higher than those on the Uncoated‐scaffold ( p < 0.05). Fe‐scaffold was found to promote the cell adhesion compared with Uncoated‐scaffold, including increasing the adhered cell number, promoting cell spreading and upregulating the expression levels of adhesion‐related genes integrin α1 and β1 and their downstream signaling molecules FAK and ERK1/2 ( p < 0.05). Moreover, the amount of new bone formed in rat calvarial defects at 8 weeks decreased in the order: Fe‐scaffold > Uncoated‐scaffold > Blank‐control (samples whose defects were left empty) ( p < 0.05). Therefore, 3D magnetic nanocomposite scaffolds enhanced the osteogenic capacities of rBMSCs in vitro and in a rat calvarial bone defect model by promoting cell adhesion. The mechanisms were attributed to the alteration in its hydrophilicity, surface roughness, and chemical composition.